Varieties of meaning : the 2002 Jean Nicod lectures - Millikan, Ruth Garrett (Jean Nicod lectures., 2004)
How the various things that are said to have meaning-purpose, natural signs, linguistic signs, perceptions, and thoughts-are related to one another.